PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK – PAIR- SHARE UNTUK MENINGKATKAN HASIL BELAJAR P.Kn SISWA KELAS V SDN 014 KASANG BANGSAWAN - Masnah '; Zariul antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The Implementation of Type of Cooperative Leaerning Model is Think – Pair- Share  planned to Increase the pupils  results at civics learning specially for grade V, State  primary school 014 kasang Bangsawan in the even Semester  cdemic year 2015/2016. This researh is done from April to May 2016, The subjects of the research are pupil and theacher, pupils minimum achievent cinterion pupils and thechers activities All of the learning activities are observed by observers, The average of the learning results for cycle I, Nam,ely 65,45 (Minus Category) and cycle II namely 89,75 (best Category). The pupils min imum for a pupil at cycle I, namely 65% (Achieved) achievement criterion and cycle II 100% (achieved). Pupils activities for cycle 87,5% (Best Category), While teacher activities for cycle I, namely 70,6 (Good Category) for cycle II, namely 91,6% (Best Category) from the research can be concluded that by implementing the type of cooperative learning model Think – Pair- Share  can be increased the pupils learning results of pupils grade fifth, State primary school 014 Kasang Bangsawan, subdistrict Pujud, district Rokan Hilir, Riau, especially at civics, academic year 2015/2016. Keywords : Pupils Activities, Tipe of Cooperatif Learning Model, TPS